Dietary patterns and socioeconomic status in Iranian adolescent girls, 2015 - Daeie-Farshbaf, Lida; Sarbakhsh, Parvin; Ebrahimi-Mamagani, Mehranghiz; Tarighat-Esfanjani, Ali (Progress in Nutrition, 2020)
Objective: Identifying major dietary patterns (DP) and their association with socioeconomic factors among adolescent girls, Tabriz, Iran. Methods: The present cross-sectional study was conducted among 725 girls aged 14-18 years, selected by multistage random sampling from 5 districts of Tabriz high schools. Participant’s socioeconomic characteristics and food intake was gathered via suitable questionnaires. Height and weight were measured and body mass index (BMI) was calculated. Dietary patterns were identified using factor analysis. Additionally, the relationship between DPs and socioeconomic factors was evaluated using generalized linear models. Results: Three major DPs were identified and labeled as western, traditional and healthy and a total variation rate of 25.84% was detected. According to the univariate model, the healthy DP was in correlation with BMI< 85th percentile (P=0.04). A significant positive association between household size less than 4 members and western (P= 0.007) and traditional (P=0.01) DPs was observed. Healthy DP had a significant association with family income ≥ 1000$ (P=0.05) and parent’s smoking situation had a significant association with Western DP (P=0.008). However after regression model analyzes, the association was only observed for family income ≥ 1000$ (ß=0.6, CI=0.21-0.99, P=0.002). Excessive usage of internet and cell phone was in correlation with the Western DP (ß=0.13, CI=0.07-0.19, P